1999
DOI: 10.1093/oxfordjournals.aje.a009899
|View full text |Cite|
|
Sign up to set email alerts
|

Power-Frequency Electric and Magnetic Fields and Risk of Childhood Leukemia in Canada

Abstract: In a case-control study of childhood leukemia in relation to exposure to power-frequency electric and magnetic fields (EMF), 399 children resident in five Canadian provinces who were diagnosed at ages 0-14 years between 1990 and 1994 (June 1995 in British Columbia and Quebec) were enrolled, along with 399 controls. Exposure assessment included 48-hour personal EMF measurement, wire coding and magnetic field measurements for subjects' residences from conception to diagnosis/reference date, and a 24-hour magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 16 publications
2
162
3
1
Order By: Relevance
“…We felt that if we could also incorporate new studies from non-European countries this pooled analysis would be up to date and presumably stay current for several years. We were aware of three more studies in other parts of the world with compatible information that were all nearly A pooled analysis of magnetic fields and childhood leukaemia completed or recently completed, so we could include those too (Linet et al, 1997;Dockerty et al, 1998Dockerty et al, , 1999McBride et al, 1999). Table 1 lists the studies and their relevant characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…We felt that if we could also incorporate new studies from non-European countries this pooled analysis would be up to date and presumably stay current for several years. We were aware of three more studies in other parts of the world with compatible information that were all nearly A pooled analysis of magnetic fields and childhood leukaemia completed or recently completed, so we could include those too (Linet et al, 1997;Dockerty et al, 1998Dockerty et al, , 1999McBride et al, 1999). Table 1 lists the studies and their relevant characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies have reported no or little association between wire -code category and childhood cancer (Linet et al, 1997;McBride et al, 1999 ) and suggestive associations between childhood cancer and measured fields . Thus, the linkage among wire -code categories, magnetic -field attributes, and health remains inconsistent and uncertain.…”
Section: Introductionmentioning
confidence: 98%
“…A study from New Zealand (Dockerty et al, 1998) found no significant increase in risk using as exposure metrics the means of two 24-h measurements made in the centre of the most used room and by the child's bed. Two recent Canadian studies (McBride et al, 1999;Green et al, 1999) found no increase in risk using 48-h personal monitoring. The influence of the body on the electric field during personal monitoring, together with the possibility that case children may have changed their behaviour since developing the disease make these results hard to interpret.…”
Section: Discussionmentioning
confidence: 90%